2019
DOI: 10.1038/s41598-019-49332-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of CD4+CD57+ senescent T cells in patients with newly diagnosed acute heart failure: exploring new pathogenic mechanisms with clinical relevance

Abstract: Recent animal studies showed t cells have a direct pathogenic role in the development of heart failure (HF). However, which subsets of T cells contribute to human HF pathogenesis and progression remains unclear. We characterized immunologic properties of various subsets of T cells and their clinical implications in human HF. Thirty-eight consecutive patients with newly diagnosed acute HF (21 males, mean age 66 ± 16 years) and 38 healthy control subjects (21 males, mean age 62 ± 12 years) were enrolled. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 32 publications
5
28
0
Order By: Relevance
“…Higher frequencies of CD4+CD57+ T-cells have been associated with poorer prognosis in several diseases. In acute heart failure patients, high percentages of these cells are associated with the development of cardiovascular events (defined as heart failure-associated mortality, transplantation, or rehospitalization) [40]. In end-stage renal disease patients, the frequency of CD4+CD57+ T-cells is associated with atherosclerotic changes [41], and in multiple sclerosis, their frequency is associated with disease severity and poorer prognosis [42].…”
Section: Notably Cmv-seronegative Individuals Had Very Low or No Percentages Of Both Cytotoxic Cd4+ T-cells (Cd1017a+) And Cd4+cd57+ T-cementioning
confidence: 99%
See 1 more Smart Citation
“…Higher frequencies of CD4+CD57+ T-cells have been associated with poorer prognosis in several diseases. In acute heart failure patients, high percentages of these cells are associated with the development of cardiovascular events (defined as heart failure-associated mortality, transplantation, or rehospitalization) [40]. In end-stage renal disease patients, the frequency of CD4+CD57+ T-cells is associated with atherosclerotic changes [41], and in multiple sclerosis, their frequency is associated with disease severity and poorer prognosis [42].…”
Section: Notably Cmv-seronegative Individuals Had Very Low or No Percentages Of Both Cytotoxic Cd4+ T-cells (Cd1017a+) And Cd4+cd57+ T-cementioning
confidence: 99%
“…In end-stage renal disease patients, the frequency of CD4+CD57+ T-cells is associated with atherosclerotic changes [41], and in multiple sclerosis, their frequency is associated with disease severity and poorer prognosis [42]. In addition, in acute heart failure patients, percentages of IFN-γ+ and TNF-α+cells are higher within the CD4+CD57+ than the CD57− T-cell subset, and CD4+CD57+IFN-γ+T-cells were increased in patients compared with healthy individuals in response to anti-CD3 stimulation [40]. In our hands, the PI of CD4+ T-cells overall and the CD4+CD57+ T-cell fraction increased with CMV-seropositivity, but not age, supporting a significant role of CMV in the development of cardiovascular disease that can be explained, at least in part, through the expansion of these proinflammatory and cytotoxic CD4+CD57+ T-cells.…”
Section: Notably Cmv-seronegative Individuals Had Very Low or No Percentages Of Both Cytotoxic Cd4+ T-cells (Cd1017a+) And Cd4+cd57+ T-cementioning
confidence: 99%
“…The hypothetical positive feedback loop described here that involves T sen and excessive inflammation and non‐specific tissue damage may also be involved in other non‐resolving inflammatory diseases where accumulation of T sen cells have been demonstrated including Chagas disease (Molina & Kierszenbaum, 1989) and malaria (Cockburn et al, 2014). The accumulation of senescent T cells with increased pro‐inflammatory potential has been implicated during age‐related diseases such as rheumatoid arthritis (Goronzy et al, 2013; Weyand et al, 2017), Alzheimer's (Gate et al, 2020), and cardiovascular diseases (Youn et al, 2019; Yu et al, 2015), where the non‐specific tissue damage driven by T sen cells needs to be investigated and might offer new opportunities for prevention and treatment (Andersson et al, 2011). Furthermore, it would important to know if inflammation that is induced by infections such as SARS‐CoV‐2 that have a disproportionate pathological impact in older individuals (Merad & Martin, 2020) results from non–specific T sen recruitment and induction of non‐antigen specific damage in the lung and other tissues.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…This subpopulation of T cells was shown to increase with age; to overexpress several SASP-related genes (i.e., like IL-10, TNFα, and IFNγ); and to proliferate less than their double-negative counterparts [ 99 , 100 , 101 ]. These cells, often referred to as senescent-like, were also found to be associated with several aged-related pathologies, such as type 2 diabetes [ 102 ], acute heart failure [ 103 ], and acute proinflammatory situations like COVID-19-exposed patients [ 104 ]. In opposition, others demonstrated that human CD57-positive and CD57-negative T cells exhibit similar proliferation properties [ 105 ].…”
Section: Age-associated Mechanisms Affecting the Efficacy Of Immunotherapymentioning
confidence: 99%